Pengaruh Modal, Tingkat Pendidikan dan Teknologi Terhadap Pendapatan Usaha Mikro Kecil dan Menengah (UMKM) Di Kawasan Imam Bonjol Denpasar Barat - Utari, Tri; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 12, Desember 2014 (pp. 549-623), 2014)
The purpose of this study was to determine the effect of capital, the level of education and technology to the SMEs in the area of ??revenue Imam Bonjol West Denpasar. This study used quantitative research is to look at the amount of capital, the level of education of the owners of SMEs and SME technology used. This study used a sample of 59 companies located in the region of West Denpasar Imam Bonjol. The data analysis technique used in this study is multiple linear regression.  It was found that capital partially positive and significant effect on the income of SMEs in the West Denpasar Imam Bonjol. The level of education and technology also have positive and significant impact on revenues partially Imam Bonjol SMEs in the West Denpasar. Simultaneously capital, level of education and technology also have positive and significant impact on the income of SMEs in the region of Imam Bonjol West Denpasar.
Keywords: Capital , Level of Education , Technology , Earnings